VULNERABILITY OF MALE BRAINS TO GLOBAL HYPOXIC ISCHEMIC BRAIN INJURY AND ESTROGEN RECEPTOR ALPHA - Zafer, Dila; Chanana, Vishal; Hanalioglu, Damla; Kareem, Samer Abdul; Al Subu, Rand; Melengic, Letisya; Serebin, Molly; Chandrashekhar, Jayadevi; Freeman, Kaylyn; Otles, Arel; Ferrazzano, Peter; Levine, Jon; et al. (LIPPINCOTT WILLIAMS \& WILKINS, 2018)
47th Critical Care Congress of the Society-of-Critical-Care-Medicine, San Antonio, TX, FEB 25-28, 2018